Precursor‐Transformation Strategy Preparation of CuPx Nanodots–Decorated CoP3 Nanowires Hybrid Catalysts for Boosting pH‐Universal Electrocatalytic Hydrogen Evolution. Issue 49 (28th October 2019) - Cheng, Yu; Pei, Yu; Zhuang, Peiyuan; Chu, Hang; Cao, Yudong; Smith, Will; Dong, Pei; Shen, Jianfeng; Ye, Mingxin; Ajayan, Pulickel M.
Abstract: The development of earth‐abundant, low cost, and versatile electrocatalysts for producing hydrogen from water electrolysis is still challenging. Herein, based on high hydrogen evolution reaction (HER) activity of transition metal phosphides, a CoP3 nanowire decorated with copper phosphides (denoted as CuP x ) nanodots structures synthesized through a simple and easily scalable precursor‐transformation strategy is reported as a highly efficient HER catalyst. By decorating with CuP x nanodots, the optimized CoP3 nanowires electrode exhibits excellent catalytic activity and long‐term durability for HER in alkaline conditions, achieving a low overpotential of 49.5 mV at a geometrical catalytic current density of 10 mA cm −2 with a small Tafel slope of 58.0 mV dec −1, while also performing quite well in neutral and acidic media. Moreover, its overall performance exceeds most of the reported state‐of‐the‐art catalysts, especially under high current density of 100 mA cm −2, demonstrating its potential as a promising versatile pH universal electrocatalyst for efficient water electrolysis. These results indicate that the incorporation of earth‐abundant stable element copper can significantly enhance catalytic activity, which widens the application range of copper and provides a new path for design and selection of HER catalysts. Abstract : CoP3 nanowires decorated with CuP x nanodots structures obtained through an oxide precursor phosphorization strategy, display superior hydrogen evolution reaction performance in alkaline medium, requiring an overpotential of 49.5 mV at 10 mA cm −2 with Tafel slope of only 58 mV dec −1, and also perform well in acidic and neutral conditions. Furthermore, the density functional theory (DFT) calculation reveals the significant role that CuP x plays in activity enhancement.